Immunometabolic Responses after Short and Moderate Rest Intervals to Strength Exercise with and without Similar Total Volume - Agostinete, Ricardo R. [UNESP]; Rossi, Fabricio E. [UNESP]; Magalhaes, Alan Jose B. [UNESP]; Rocha, Ana Paula R. [UNESP]; Parmezzani, Sergio S. [UNESP]; Gerosa-Neto, Jose [UNESP]; Cholewa, Jason M.; Lira, Fabio S. [UNESP] (Frontiers Media Sa, 2016)
This study investigated the influence of short and moderate intervals of recovery with and without equated volume during an acute bout exhaustive strength exercise on metabolic, hormonal and inflammatory responses in healthy adults. Eight physically active men (23.5 +/- 3.1) performed three randomized sequences: Short (70% of 1 RM with 30s of rest): Moderate (70% of 1 RM with 90s of rest): and Volume-Equated Short (70% of 1 RM with 30s of rest between sets with a repetition volume equal to that performed in Moderate). All sequences of exercises were performed until movement failure in the squat, bench press and T-bar row exercises, respectively. Glucose, lactate, testosterone, IL-6, IL-10, IL-1ra, and MCP-1 levels were assessed at rest, immediate post-exercise, and 1 h post. There was a main effect of time for testosterone (p < 0.001). The post hoc indicated differences between post exercise and rest and post-1 h and post-exercise (p < 0.001). Lactate increased post-exercise when compared to pre and post-1 h (p < 0.001) and maintained higher post-1 h in relation to rest. IL-6 was greater post-exercise than rest (p = 0.045) and post-1 h and rest (p = 0.020). IL-10 was greater post exercise (p = 0.007) and post-1 h (p = 0.002) than rest. IL-1ra increased post-exercise in relation to rest (p = 0.003) and MCP-1 was greater post-exercise than rest (p < 0.001) and post-1 h (p = 0.043). There were no significant differences between conditions or interaction. Thus, both short and moderate intervals of recovery induced greater metabolic, hormonal and inflammatory responses after acute bout of exhaustive strength exercise in healthy adult.
Keywords: strength exercise; intervals of recovery; testosterone; inflammation; metabolism